Sensory Characteristics of Tauco with Lemon Extract as Natural Preservative - Paulus Damar Bayu Murti; Sia Clarissa Eleora Setiawan; Lusiawati Dewi (Food ScienTech Journal, 2026)
Tauco is a traditional Indonesian fermented soybean paste product offering nutritional and sensory benefits, however has a relatively short shelf-life. In this study, we used lemon extract as a natural preservative to extend the shelf-life of tauco while maintaining its sensory acceptability. Six tauco formulations were prepared in the following one control and five treatments with lemon extract concentrations of 0.1%, 0.2%, 0.3%, 0.4%, 0.5% respectively. A total of 20 untrained panelists conducted a sensory evaluation using a 5-point scale preferability from “very dislike” to “very like” to evaluate color, aroma, taste, texture, and overall acceptability.  By using lemon extract, particularly at 0.3% to 0.5% can effectively extends the shelf-life of tauco by reducing microbial activity and preserving quality attributes. It reveals a promising natural preservation method for fermented soybean products that meets consumer demand for clean-label ingredients.